New records of hagfishes (Myxini: Myxiniformes: Myxinidae) from the Pacific coast of Costa Rica - Cruz Mena, Oscar Isaac (2015)
A specimen of the Pacifi c hagfi sh, Eptatretus stoutii (Lockington, 1878), 351 mm total length, and four specimens of the whiteface hagfi sh, Myxine circifrons Garman, 1899, 400–545 mm total length, were collected between 1987 and 2010 from off the Pacifi c coast of Costa Rica at depths ranging from 80 to 825 m. The speci men of E. stoutii represents the fi rst record of the species in Costa Rican and Central American waters, as well as a southeast range extension of about 3500 km on the known distribution of the species; the specimens of M. circifrons represents the second documented record of this species in Costa Rican waters. In this paper these new records are reported and discussed; a brief description of the specimens as well as comparative morphometric and meristic data are provided